The Neglected Ethical and Spiritual Motivations in the Workplace - Guillén, Manuel (Journal of business ethics, 2015)
Understanding what motivates employees is essential to the success of organizational objectives. Therefore, properly capturing and explaining the full range of such motivations are important. However, the classical and most popular theories describing employee motives have neglected, if not omitted entirely, the importance of the ethical and spiritual dimensions of motivation. This has led to a model of a person as self-interested, amoral, and non-spiritual. In this paper, we attempt to expose this omission and offer a more complete taxonomy of motivations which include these dimensions. Although more work will need to be done to fully develop the ethical and spiritual dimensions of motivation, the expanded taxonomy will provide the foundations and serve as a guide for such further research. Furthermore, this new categorization of motivations brings out the full dimensions of being human, which promises to lead to improved management practices with regard to employees and foster greater human flourishing in the workplace.